Carbon acquisition characteristics of six microalgal species isolated from a subtropical reservoir: potential implications for species succession. Issue 5 (12th September 2018) - Lines, Thomas; Beardall, John
Abstract : CO2 levels in freshwater systems can fluctuate widely, potentially influencing photosynthetic rates and growth of phytoplankton. Given the right conditions, this can lead to bloom formation and affect water quality. This study investigated the acquisition of dissolved inorganic carbon (DIC) by six species of microalgae, a cyanobacterium Cylindrospermopsis raciborskii, the diatoms Cyclotella sp., Nitzschia sp., and the green algae Stichococcus sp., Staurastrum sp., and Monoraphidium sp., all isolated from a subtropical reservoir in Australia. Carbon acquisition characteristics, specifically the affinity for DIC, internal pH, and internal DIC concentrations were measured. Affinities for CO2 ( K 0.5 ( CO 2 ) ) ranged between 0.7 and 6 μM CO2 . This was considerably lower than air‐equilibrated surface water CO2 concentrations, and below reported affinities for CO2 of RuBisCO suggesting operation of active carbon dioxide concentrating mechanisms (CCMs) in all species. Internal pH was lowest for Cyclotella sp. at 7.19, and highest for Staurastrum sp., at 7.71. At 180 μM external DIC, ratios of internal:external CO2 ranged from 2.5 for Nitzschia sp. to 14 in C. raciborskii . Internal HCO3 − concentration showed a linear relationship with surface area to biovolume ratio (SA:Vol). We hypothesized that species with a higher SA:Vol suffer more from diffusive escape of CO2, thus storage of DIC as bicarbonate is favored in these strains. For C. raciborskii, under stratified summer conditions, its strong CCM, and resilient photosynthetic characteristics may contribute to its bloom forming capacity.